HOMOPOLYMERIZATION OF POLY(DIMETHYLSILOXANE) MACROMONOMERS VIA FREE RADICAL POLYMERIZATION - A. Morales-Cepeda (Revista Mexicana de Ingeniería Química, 2007)
Hompolymers of poly(dymethylsiloxane) terminated with one methyl methacrylate end group (PDMS-MA) weresynthesized by conventional free radical polymerization. The crucial step to polymerize the commercial PDMSMAmacromonomers was their purification using a free radical pre-polymerization technique. The separation ofhomopolymer and unreacted PDMS-MA macromonomer was achieved by precipitation in a mixture of diethylether/methanol (1:1). Kinetic studies of homopolymerization yielded the ratio between rate of propagation andtermination (kp/kt½). This ratio decreased with increasing the molecular weight of the macromonomers. Theapparent rate of propagation was proportional to [I]2.2 and [M] for appropriate polymerizations conditions. Theceiling temperature were calculated for macromonomers with Mn = 1 and 5 Kg/mol, to be Tc= 160°C at [M1]= 0.88and [M5]= 0.11 mol/L, for both homopolymers.